2018
DOI: 10.1080/14643154.2018.1437238
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and real-world estimation abilities of deaf and hearing college students

Abstract: Various studies have examined possible loci of deaf learners’ documented challenges with regard to reading, usually focusing on language-related factors. Deaf students also frequently struggle in mathematics and science, but fewer studies have examined possible reasons for those difficulties. The present study examined numerical and non-numerical (real-world) estimation skills among deaf and hearing college students, together with several cognitive abilities likely to underlie mathematics performance. Drawing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…However, in this group, higher scores on the sarcasm stories were predicted by superior performance on the WJ-III Spatial Relations test. While the reasons for this dissociation are unclear, several other studies involving deaf and hearing college students engaged in cognitive tasks have found different predictors for the two groups (e.g., Borgna et al, 2018;Marschark et al, 2017;Marschark, Spencer, et al, 2015). The extent to which such differences derive from hearing status, language ability, educational background, or some other factor(s) remains to be determined.…”
Section: Discussionmentioning
confidence: 94%
“…However, in this group, higher scores on the sarcasm stories were predicted by superior performance on the WJ-III Spatial Relations test. While the reasons for this dissociation are unclear, several other studies involving deaf and hearing college students engaged in cognitive tasks have found different predictors for the two groups (e.g., Borgna et al, 2018;Marschark et al, 2017;Marschark, Spencer, et al, 2015). The extent to which such differences derive from hearing status, language ability, educational background, or some other factor(s) remains to be determined.…”
Section: Discussionmentioning
confidence: 94%
“…They need learning methods that can display concrete following what they have experienced. The mathematical learning approach that suits their (Borgna et al, 2018). They also need to be taught using rich concrete language, and teachers need to prevent them from fantasizing about the unknown.…”
Section: Selective Codingmentioning
confidence: 99%